2018
DOI: 10.1007/s00276-018-2005-5
|View full text |Cite
|
Sign up to set email alerts
|

The retromolar canals and foramina: radiographic observation and application to oral surgery

Abstract: Hypoesthesia of the buccal gingiva in the lower molar region may be the main complication when the RMC is damaged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 20 publications
2
39
0
Order By: Relevance
“…In studies by other authors, RMC was observed in 13/50 patients (26%), with confirmed double RMC [14] in 3.4% [10] and 23% [23] of cases, respectively.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In studies by other authors, RMC was observed in 13/50 patients (26%), with confirmed double RMC [14] in 3.4% [10] and 23% [23] of cases, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…3). Other authors also concluded that type B1 is the most common type of RMC found in 66.7% of cases, compared to type A1 -26.7 [14]. Other studies, however, point to type A1 as the most dominant (41.9%), followed by B1 -29%, A1 -16.1%, B2 -12.9% [25].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies of clinical cases using CBCT images have shown that the prevalence of retromolar canals (RMCs) ranges from 8.5% to 75.4%. However, cadaveric studies have reported a prevalence ranging from 8.3% to 52.0% using CBCT images, and 8.0% to 40.4% with microscopy (Kikuta et al ). The RMC's average diameter was 1.58 mm (range, 1.13–2.24 mm) (Kuribayashi et al ; Senthil Kumar and Kesavi ; Han and Hwang ; Muinelo‐Lorenzo et al ; Capote et al ; Sisman et al ; Motamedi et al ).…”
Section: Literature Review and Suggestions For Risk Assessment Of Injurymentioning
confidence: 99%
“…The mandible's anatomical variations, for example, those in the accessory mental, lingual, retromolar, and accessory mandibular foramina, and double mandibular canal (Das and Suri ; Rouas et al ; Imada et al ; Iwanaga et al ; He et al ; Kikuta et al ) can lead to unexpected surgical complications when they are overlooked in preoperative diagnosis, the most common of which in clinical dentistry are hemorrhage and paresthesias. For more than a decade, a number of anatomical, radiological, and clinical studies have shown the potential complications caused by such variants' injury that are not always symptomatic, although some may cause symptoms as well as major disorders.…”
Section: Introductionmentioning
confidence: 99%